Salivary cortisol and testosterone responses to high-intensity cycling before and after an 11-day intensified training period - Hough, J.; Corney, R.; Kouris, A.; Gleeson, M. (Journal of Sports Sciences, 2013)
This study examined salivary cortisol and testosterone responses to two, different high-intensity, 30-min cycles separated by 2 h rest before and after an 11-day intensified training period. Twelve recreationally active, healthy males completed the study. Saliva samples were collected before, immediately after and 30 min after both bouts with salivary cortisol and testosterone concentrations assessed. Compared with pre-training blunted exercise-induced salivary cortisol, testosterone and cortisol/testosterone responses to both bouts post-training were observed (P < 0.05 for all). Comparing pre- with post-training the absolute exercise-induced salivary cortisol, testosterone and cortisol/testosterone decreased from 11.1 to 3.1 and 7.0 to 4.4 nmol/L (cortisol), from 407 to 258 and from 473 to 274 pmol/L (testosterone) and from 12 to 4 and 7 to 5 (cortisol/testosterone) for the first and second bouts, respectively (P < 0.05). No differences in the pre- and post-training rating of perceived exertion (RPE) and heart rate (HR) responses during the cycles or times to fatigue were found (P > 0.05). Fatigue and Burnout scores were higher post- compared with pre-training (P < 0.05).